Selective Laser Melting of Metal Powders Studied by Molecular Dynamics Simulation - Tang, C. (2016)
Selective laser melting can be used to build up 3D metal parts by melting metallic powders together. In this paper, we performed molecular dynamics simulation to investigate the selective laser heating process of Cu powders. Cu atoms were heated up by a mobile laser beam and subsequently cooled down by a Ni-base plate underneath them. Radial distribution function analysis revealed that Cu atoms are melted by the laser irradiation. Additionally, our results showed that Cu atoms around the laser beam are fused together.